Physical fitness profiles of football players across competitive levels in southeast asia: a systematic review - Vega Soniawan; Ikhwanul Arifan (JRTI (Jurnal Riset Tindakan Indonesia), 2025)
Football is the most widely practised team sport in Southeast Asia, yet regional teams continue to underperform relative to international benchmarks, and the physical fitness evidence underpinning player development remains fragmented across countries and competitive tiers. This systematic review synthesises how physical fitness has been characterised among football players in Southeast Asia and how the reported profiles differ across competitive levels. The review followed the PRISMA 2020 framework. A Boolean search of Scopus using TITLE-ABS-KEY, combining football, physical fitness and Southeast Asian country terms, retrieved 4,122 records. Eligibility was restricted to English-language journal articles published in final stage between 2021 and 2025 that reported at least one standardised physical fitness outcome for football players sampled in a Southeast Asian country; reviews, non-player populations and studies without fitness outcomes were excluded. After duplicate removal, filtering and screening, 53 reports were assessed in full text and 22 studies were included. Aerobic capacity and linear speed dominated the evidence base, whereas flexibility, balance and anaerobic power were rarely profiled, and professional and female cohorts were markedly underrepresented. The findings support level-specific testing batteries and a harmonised regional normative database, and future work should prioritise longitudinal, cross-level and female-focused designs.